A cis-element at the Rorc locus regulates the development of type 3 innate lymphoid cells - Chang, Dehui; Zhang, Hao; Ge, Jing; Xing, Qi; Guo, Xinyi; Wang, Xiaohu; Dong, Chen (Frontiers in Immunology, 2023)
As an important early source of IL-17A and IL-22 in immune responses, type 3 innate lymphoid cells (ILC3s) are critically regulated by the transcription factor retinoic-acid-receptor-related orphan receptor gamma t (RORγt). Previously, we have identified a crucial role of the conserved non-coding sequence 9 (CNS9), located at +5,802 to +7,963 bp of the Rorc gene, in directing T helper 17 differentiation and related autoimmune disease. However, whether cis-acting elements regulate RORγt expression in ILC3s is unknown. Here we show that CNS9 deficiency in mice not only decreases ILC3 signature gene expression and increases ILC1-gene expression features in total ILC3s, but also leads to generation of a distinct CD4+NKp46+ ILC3 population, though the overall numbers and frequencies of RORγt+ ILC3s are not affected. Mechanistically, CNS9 deficiency selectively decreases RORγt expression in ILC3s, which thus alters ILC3 gene expression features and promotes cell-intrinsic generation of CD4+NKp46+ ILC3 subset. Our study thus identifies CNS9 as an essential cis-regulatory element controlling the lineage stability and plasticity of ILC3s through modulating expression levels of RORγt protein.